Web-Based Library Information System at SDN 2 Cerme Kidul - Marthanugraha, Rizki (Politeknik Negeri Malang, 2024)
The library transaction process at SDN 2 Cerme Kidul is carried out by utilizing data from this web-based application. Library operations, including membership procedures, borrowing, and returning books, are managed through this application. This website is designed to handle these processes while supporting master data management, assisting library book collection management, facilitating book searches through catalogs, and presenting reports related to book collections. The creation of this website uses the waterfall system development method, which involves data collection through interviews, observations, and literature studies. Analysis is carried out on aspects of users, technology, needs, data, systems, information, performance, and system design using flowcharting diagrams. Website development utilizes the PHP programming language, MySQL database, Apache local server, and Sublime Text editor. For testing, black box testing and beta testing methods are used. This library application provides many benefits, such as helping librarians improve work efficiency, speeding up the process of borrowing and returning books, calculating fines faster, and making it easier for library users to access information related to the library.